Enzyme replacement therapy and white matter hyperintensity progression in Fabry disease. (9th October 2018) - Stefaniak, James D.; Parkes, Laura M.; Parry-Jones, Adrian R.; Potter, Gillian M.; Vail, Andy; Jovanovic, Ana; Smith, Craig J.
Abstract : Objective: To explore the association between enzyme replacement therapy (ERT), clinical characteristics, and the rate of progression of white matter hyperintensities (WMH) in patients with Fabry disease (FD). Methods: Patients with a confirmed diagnosis of FD, aged 18 years or older, participating in an existing FD observational study (NCT00196742), with at least 2 serial MRI brain scans at least 2 years apart for the period between December 2006 and August 2016 were included in this cohort study. Total WMH volume was estimated for each image using a semiautomated procedure. We performed linear regression to calculate the primary outcome measure of WMH change rate for each participant. Associations between ERT, clinical characteristics, and the primary outcome were explored using multiple linear regression. Results: Eight hundred sixty-three MRI time points were analyzed for the 149 included participants. Age ( p < 0.0005; increasing age associated with faster WMH progression), total cholesterol ( p = 0.03; increasing total cholesterol associated with slower WMH progression), and a history of peripheral pain ( p = 0.02; peripheral pain associated with faster WMH progression) were independently associated with WMH change rate in the primary analysis. We did not find an association between "ERT at any point between baseline and final MRI" and WMH change rate ( p = 0.22). Conclusion: In a large cohort of patients with FD, we did not find an association between ERT and WMH progression, while higher total cholesterol was associated with slower WMH progression. Further research is needed into the pathogenesis and treatment of cerebrovascular disease in this rare condition.